Analisis Perilaku Nasabah Terhadap Produk Tabungan Pelajar PT. Bank Rakyat Indonesia (Persero) Unit Simalingkar - Tarigan, Delianta Natalia Anjeli; Purnasari, Nina (Jurnal Ekonomi Bisnis Digital, 2022)
This study entitled "Analysis of Customer Behavior on Student Savings Products at PT. Bank Rakyat Indonesia (Persero) Tbk. Simalingkar Units”. One of BRI's savings products is student savings (Junio). The purpose of the Student Savings (Junio) is so that children love to save, and also teach them how to manage their pocket money. With the Student Savings (Junio) which is one of the products intended for children under the age of 17 years. Student Savings is also aimed at children based on age classification, ranging from PAUD, Kindergarten, SD, SMP, SMA so that they can know the bank from an early age. The type of this research that was conducted was field research and the nature of the research was descriptive, data collection was also carried out with two techniques, namely observation and interview techniques. The research data also shows that the product strategy in increasing the number of customers to save student savings is also applied by Bank Rakyat Indonesia Unit Simalingkar Medan on student savings(Junio) by applying the concept of product strategy, pricing, promotion, and marketing to offer student savings products. (Junio) to people who don't know about student savings (Junio).